The Self- and Peer-Assessments in Creative Writing: Students’ Benefits and Reactions - Ni Putu Agustina Konita Dewi; Putu Kerti Nitiasih; Made Hery Santosa (Soshum: Jurnal Sosial dan Humaniora, 2024)
This research is aimed at fostering students’ reflective efforts by providing self- and peer-assessment approaches during the process of learning how to write creative writing about Indonesian narrative stories. The implementation of this instructional method promotes students' writing proficiency, critical thinking abilities, and autonomy. The objective of this research is to introduce, explore the advantages of, and evaluate students' reactions to self-and peer assessment in a writing course. A case study design was employed, focusing on tenth-grade EFL students in SMAN 8 Denpasar. They were chosen by purposive random sampling. The research utilized various methods such as open-ended questionnaires and in-depth interviews. The analysis of the data reveals the positive outcomes associated with peer- and self-assessment. The findings suggest that English teachers should employ this instructional approach to enable students to fully engage in the writing process and enhance their writing skills.